Structural insights into the interaction of papain‐like protease 2 from the alphacoronavirus porcine epidemic diarrhea virus and ubiquitin. Issue 7 (18th June 2021) - Durie, Ian A.; Dzimianski, John V.; Daczkowski, Courtney M.; McGuire, Jack; Faaberg, Kay; Pegan, Scott D.
Abstract : Coronaviruses encode a papain‐like protease (PLP) which is responsible for antagonizing the innate immune response; here, the structure of the first known Alphacoronavirus PLP bound to ubiquitin, its preferred substrate, is reported. Abstract : Porcine epidemic diarrhea is a devastating porcine disease that is caused by the alphacoronavirus porcine epidemic diarrhea virus (PEDV). Like other members of the Coronaviridae family, PEDV encodes a multifunctional papain‐like protease 2 (PLP2) that has the ability to process the coronavirus viral polyprotein to aid in RNA replication and antagonize the host innate immune response through cleavage of the regulatory proteins ubiquitin (Ub) and/or interferon‐stimulated gene product 15 (ISG15) (deubiquitination and deISGylation, respectively). Because Betacoronavirus PLPs have been well characterized, it was sought to determine how PLP2 from the alphacoronavirus PEDV differentiates itself from its related counterparts. PEDV PLP2 was first biochemically characterized, and a 3.1 Å resolution crystal structure of PEDV PLP2 bound to Ub was then solved, providing insight into how Alphacoronavirus PLPs bind to their preferred substrate, Ub. It was found that PEDV PLP2 is a deubiquitinase and readily processes a variety of di‐Ub linkages, in comparison with its Betacoronavirus counterparts, which have a narrower range of di‐Ub activity but process both Ub and ISG15.